Pre-exposure prophylaxis (PrEP) awareness, attitudes and uptake willingness among young people: gender differences and associated factors in two South African districts - Simukai Shamu; Patience Shamu; Sikhulile Khupakonke; Thato Farirai; Thato Chidarikire; Geoffrey Guloba; Nkhensani Nkhwashu (Taylor & Francis Group, 2021)
Background: Pre-exposure prophylaxis (PrEP) for HIV prevention is safe and effective in reducing HIV incidence. However, more evidence of PrEP knowledge, willingness and distribution preferences is required for scale-up among young people at-risk. Objective: To understand young people PrEP awareness, willingness and roll-out preferences. Methods: Young people (18-24y) were selected through multi-stage sampling in a cross-sectional household survey in low-income communities. Self-administered interviews collected participants' data about PrEP awareness, attitudes, willingness and HIV-risk practices. Data were descriptively analysed by gender. Regression models assessed factors associated with PrEP awareness and willingness by district. Results: Of the 1917 participants interviewed 44.6% (men = 39.4% vs women = 49%, p = 0.001) were PrEP aware, 49.0% were willing to use PrEP. Participants most preferred PrEP distribution channels were public clinics (51.2%) and hospitals (23.8%). More men than women preferred distribution through schools (11.9% vs7.8%; p = 0.002) and NGOs (8.5%vs5.4%; p = 0.008). The biggest barrier to PrEP willingness was inadequate PrEP knowledge (10.0%) but more men than women disliked taking pills daily (4.1%vs2.0%; p-value = 0.007). Gendered determinants to use PrEP were side effects (51%; men = 47% vs women = 55%; p = 0.001) and pill effectiveness (29.5%; men = 26.4% vs women = 32.6%; p = 0.003). In both districts PrEP knowledge was associated with being female and media use. The associations between PrEP awareness and having multiple sexual partnerships, HIV knowledge, HIV self-test willingness and belonging to social clubs differed by district. PrEP willingness was positively associated with having TB and PrEP knowledge in each district but district differences were observed in media and occupation factors. Conclusions: The study shows young people's low levels of PrEP awareness. It also shows relatively increased willingness, gendered PrEP awareness and distribution preferences. Promoting youth's PrEP awareness requires a multifarious media strategy. Abbreviations: HIV: human immunodeficiency virus; AIDS: Acquired immunodeficiency syndrome; aOR: Adjusted Odds ratio; PLWH: People living with HIV; PrEP: Pre-exposure Prophylaxis; UNAIDS: Joint United Nations Programme on HIV and AIDS; uOR: Unadjusted odds ratio; TB: Tuberculosis; WHO: World health Organisation; MSM: Men who have sex with men